Prognostic value of achilles tendon doppler sonography in asymptomatic runners - Hirschmüller, A.; Frey, V.; Konstantinidis, L.; Baur, H.; Dickhuth, H.-H.; Südkamp, N. P.; Helwig, P. (Medicine & Science in Sports & Exercise, 2012)
Introduction: Midportion Achilles tendinopathy (MPT) is a common problem in running athletes. Nevertheless, its etiology is not fully understood, and no valid prognostic criterion to predict the development of MPT could be identified to date. The purpose of the present study, therefore, was to evaluate whether power Doppler ultrasonography (PDU) is a suitable method to identify a predisposition to MPT in yet asymptomatic runners.